P111 Extracellular Nicotinamide Phosphoribosyltransferase (eNAMPT): A possible new target in inflammatory bowel diseases. (16th January 2018) - Travelli, C; Colombo, G; Porta, C; Malavasi, F; Genazzani, A A
Abstract: Background: Nicotinamide phosphoribosyltransferase (NAMPT) is present in two different forms: an intracellular form, called iNAMPT and an extracellular form eNAMPT. iNAMPT catalyses the production of nicotinamide mononucleotide, precursor of NAD, therefore essential for the control of metabolism (Chiarugi et al., 2012). The extracellular form, eNAMPT is a cytokine with paracrine and autocrine effects on different cell types, however the mechanism of action is still unknown. Importantly, iNAMPT expression and eNAMPT levels are increased in several pathologies, included inflammatory bowel diseases (IBD). In particular, the levels of NAMPT correlate with the stage of the pathology, indeed in an active state of the disease the levels of NAMPT are very high, and importantly its levels are partially reduced in a remission stage (Moschen et al., 2007). In ulcerative colitis (UC) there is an unbalance of pro-inflammatory and anti-inflammatory macrophages, with a predominance of the pro-inflammatory pool. Abundant inflammatory stimuli are able to increase iNAMPT expression and eNAMPT over-secretion, especially from innate immune cells such as neutrophils, monocytes, macrophages. The aim of our work was to determine the role of eNAMPT and its neutralisation in ulcerative colitis. Methods: Two in vivo models were used: the DSS− and DNBS− model. DSS was given orally to C57bl/6 mice for 6 days, and mice were sacrificed at day 10 or 16. In the DNBS model, Balb/c mice were injected intrarectally with DNBS and mice were sacrificed after 5 days. Mice were treated with a control IgG1 or eNAMPT antibody (50 µg/mouse, every 3 days). Blood, spleen, colon, and lymph nodes were collected and analysed for ELISA, IHC, gene expression and flow cytometry analysis. Mouse peritoneal exudate cells (PEC) were obtained from peritoneal lavage in C57bl/6 mice. Results: We found that NAMPT is induced in PEC upon the stimulation with IFNγ and LPS, while IL-4 failed to evoke NAMPT expression and secretion. Moreover, the stimulation with the eNAMPT sustains a M1 polarisation state of the macrophages, prompt NAMPT as a crucial cytokine in the inflammatory state. We found that iNAMPT and eNAMPT are increased in colon and serum of UC mice compared with control and more important the levels of iNAMPT/eNAMPT are reduced after the treatment with NAMPT neutralising antibody. Furthermore, the treatment reduced also the body weight loss, the colon length shortening and the damage of tissue. Conclusions: Taken together, our data demonstrated that eNAMPT is increased in serum of UC mice, and that eNAMPT neutralisation ameliorates the colitis symptoms. These data support the idea that eNAMPT could be a druggable target in this pathology.